2022
DOI: 10.21203/rs.3.rs-2103365/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonlinear Rayleigh wave propagation in thermoelastic media in dual-phase-lag.

Abstract: A model of generalized thermoelasticity within dual-phase-lag is used to investigate nonlinear Rayleigh wave propagation in a half-space of a transversely isotropic elastic material. It is assumed that the coefficient of heat conduction is temperature-dependent, a fact that plays an important role in the coupling behaviour analysis of thermoelastic and piezo-thermoelastic solids. Taking such a dependence into account becomes a necessity at higher temperatures, when the material properties can no longer be cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Figures 4 and 5 are devoted to the comparison of solutions at the first and the second orders of approximation respectively between the cases of a half-space with/without slab. The results for the half-space without slab were recently published by the same authors 20 . According to these figures, we concluded that the presence of the bonded slab yields faster attenuation of the solution with depth.…”
Section: Numerical Results and Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Figures 4 and 5 are devoted to the comparison of solutions at the first and the second orders of approximation respectively between the cases of a half-space with/without slab. The results for the half-space without slab were recently published by the same authors 20 . According to these figures, we concluded that the presence of the bonded slab yields faster attenuation of the solution with depth.…”
Section: Numerical Results and Discussionmentioning
confidence: 97%
“…An earlier work by the authors 20 has been extended to the case of a layered thermoelastic medium consisting of a thick layer rigidly bonded to a half-space. On one hand, this allows to assess the effect of the slab on wave propagation in the half-space.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations